Diagnosis and Prognosis Based On the Vibration Analysis of Rotating Machines: Study of a Vibration Test Bench - Imad El Adraoui, Hassan Gziri, Ahmed Mousrij (International Journal of Advanced Science and Technology, 2020)
This paper treated the presentation of an experimental device called vibratory test bench (Motor, shaft, wheel) which allows to test, verify and validate methods related to the evaluation, diagnosis and prognosis of unbalance phenomenon health. Balancing of the wheel (disc) is justified by the fact that most failures of rotating machines are linked to several faults among which there is unbalance. Consequently, the system can be considered critical since their failure considerably reduces the availability and safety of the machine, in particular the rotating elements, namely the guide bearings. The main objective of this work is to provide real data relating to the accelerated degradation of the wheel (disc) carried out under variable and/or constant operating conditions, capable of data the overall behavior of the system thanks to a system of acquisition to diagnose and prognosticate it. The operating conditions are characterized and detected by a piezoelectric sensor (accelerometer). In the vibration test bench, the monitoring of the system state is ensured by the online collection of a vibration signal for two different cases: without and with unbalance for different speeds of rotation. Finally, the monitoring data provided by the sensor can be used for further processing in order to extract the relevant characteristics, to assess, diagnose and permanently predict the state of health of the system.